Characterization of Moroccan populations of Trifolium and Lotus species - Bennani K.; Al Faïz C.; Thami Alami I.; Bendaou N. (The contributions of grasslands to the conservation of Mediterranean biodiversity, 2010)
Annual forage legumes are an important resource for pasture improvement. They may be used to reduce erosion and improve grazing on marginal areas. In this study, we report morphological and biometrical evaluation of 70 populations belonging to 11 species of Trifolium and Lotus collected in different Moroccan regions. Plant height, leaf size, flowering time, flowering length, number of inflorescences per plant, seeds per inflorescence, 1000 seeds weight, seed plant production and dry matter yields were determined. High variability has been shown among and within species, especially for dry matter yield and flowering time. The morphological and agronomic variables were used to group studied populations by using a principal components analysis. Populations of T. isthmocarpum and L. corniculatus produced the highest biomass.
13. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM International Network for the Research and Development of Pasture and Forage Crops, 2010/04/07-10, Alicante (Spain)